A Comprehensive Review on Human Stress Analysis Using Brain Signals - Sharma, Ruchi; Chopra, Khyati (International Journal of Psychosocial Rehabilitation, 2020)
During stressful situations or in panic states, the human brain gets activated . The central nervous system gets activated and transmits signals to other body organs. The signal generated in the brain known as neural signal could be used to detect the presence of stress. Through Electroencephalography, neural signals could be obtained which can characterize the stress state in human brain. EEG works well for the detection of various brain diseases.The Electroencephalograph signals are random, complex and non linear in nature, so they cannot be used directly but need some preprocessing. This paper reviews the work done till now to measure the stress from EEG signals. Various parameters and measures from previous studies have been taken into account in this paper.